Analysis of thyroid neoplasms in Brazilian women between 2013 and 2023: epidemiological study (Revista Científica Integrada, 2025)
Objective: To analyze epidemiological data on thyroid neoplasms in women in Brazil between 2013 and 2023. Methods: This is an epidemiological, quantitative, and exploratory study carried out with information from SISCAN, SIM, and the ICD-10 Mortality Monitoring Panel, based on the following variables: region and Federative Unit (UF) of diagnosis, age group, therapeutic modality, treatment time, color/race, marital status, and place of death. Results: A total of 39,550 women were diagnosed between 2013 and 2023, with 2023 being the year with the highest number of cases (n = 8,312), with emphasis on the southeast region of the country (43.09%). This neoplasm was more prevalent in women aged between 50 and 54 years old (24%). During the period analyzed, the total number of women who died from the disease was equivalent to 15.09% (n = 5,971) of the number of female diagnoses of thyroid neoplasia. Conclusion: The number of diagnoses of thyroid neoplasia in women increased by 5,541% from 2013 to 2023. However, female mortality in each year remained close to the average value for the period (542 deaths/year). Therefore, primary prevention, through the adoption of healthy lifestyle habits, screening techniques and monitoring of the population at risk, associated with appropriate staging and classification, as well as periodic active surveillance of low-risk nodules, are the safest and most conservative strategies to ensure the quality of life of the population and reduce unfavorable outcomes.
Keywords: Epidemiology; Thyroid Neoplasms; Women; Public Health Surveillance; Health Information Systems